α-4 subunit of nicotinic acetylcholine receptor polymorphisms exhibit no association with smoking behavior among Malay Males in Kelantan, Malaysia - A.B. Ruzilawati; N.I. Abd Rozak; A.B. Norsuhaily; A. Imran (Egyptian Journal of Medical Human Genetics, 2016)
Background: Smoking behavior is influenced by both genetic and environmental factors. Nicotine is the major addictive substance in cigarettes. Nicotinic acetylcholine receptors (nAChRs) are thought to play an important role in nicotine addiction of smokers. One of the genes, α-4 subunit of nicotinic acetylcholine receptor (CHRNA4) gene was reported to be associated with smoking behavior in many populations. Aim: The aim of this study is to determine association between α-4 subunit of nicotinic acetylcholine receptor single nucleotide polymorphism (rs2236196 and rs2273502 loci) and smoking behavior among Malay Males. Methods: The study was conducted in Malay smokers (n = 248) and non-smoking controls (n = 248). DNA was extracted from leucocytes and the two SNPs were determined by a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The PCR product was digested with restriction enzymes AfeI and Sau96I, respectively. Results and conclusion: We found that the AA genotype frequency for CHRNA4 rs2236196 polymorphism in the smoker group was 80.6% while in nonsmoker 77.0%. No mutation (GG genotype) was detected in both groups. The AG genotype for the smoker group was 19.4% while in the nonsmoker group 23.0%. There was no significant difference observed in the genotype (χ2 = 5.106, p = 0.078) and allele frequencies between both study groups. On the other hand, no mutation of CHRNA4 rs2273502 (TT genotype) was detected in the non-smoker group while the frequencies of genotype CC and heterozygous CT in non-smokers were 75.8% and 24.2%, respectively. In the smoker group, the frequencies were 73.4%, 2.0% and 24.6%, for TT, CC and CT, respectively. There was no significant difference observed in rs2273502 (χ2 = 5.16, p = 0.078) and smoking behavior of the subjects. In conclusion, the results revealed that CHRNA4 rs2273502 and rs2236196 gene polymorphisms are not statistically significantly associated with smoking behavior in our population.